On Communication. An Interdisciplinary and Mathematical Approach - Klüver, Jürgen; Klüver, Christina (Theory and Decision Library A, Rational Choice in Practical Philosophy and Philosophy of Science, 2007)
This book offers a radical new approach for the understanding of communication. By using the theoretical framework of complex systems theory communication is defined as the interplay of social and cognitive dynamics: communicators are modelled as complex cognitive systems who interact according to social rules and generate communicative systems. Messages generate meaning, which is understood as an attractor in the cognitive system of the receiver. Information is measured via the difference between a factual message and the message expected by the receiver. These theoretical definitions are operationalized by the application of certain computer programs, namely Soft Computing programs like cellular automata and artificial neural nets. In many examples the authors demonstrate how it is possible to model and analyze communicative processes, i.e. social combined with cognitive ones. The computational models are validated by social experiments that show how communicative complexity can be simulated and in some parts prognosticated. The considerations of the book are finally systematized by general equations of communication. The book refers to readers of different disciplines like communications science, social sciences, cognitive sciences and computer science. Yet no special knowledge in these sciences and/or mathematics is presupposed. Scholars of these sciences and graduate students should have no principal difficulties with the text.